Kandungan Protein dan Daya Terima Minuman Fungsional Berbasis Kacang Gude dan Tempe - Hijrah Asikin; Chaerunnimah Chaerunnimah (Jurusan Gizi Poltekkes Kemenkes Makassar, 2022)
Local food functional drink made from gude beans and tempeh is one of the efforts to diversify food which is expected to provide benefits in overcoming nutritional problems in the community. This study aims to determine the protein content and acceptability of functional drinks based on gude and tempeh. This research is a pre-experimental study with three treatments, namely the formula of gude beans and tempeh, respectively 14%, 16% and 20%. Acceptance using organoleptic test with the number of panelists as many as 30 people while the protein content using the micro kjeldahl test. Data analysis used Two Way Anova Test with Duncan's follow-up test. The results of the assessment showed that the most preferred formula was the one that contained 16% gude and tempeh flour. The average result of acceptance based on all aspects of the three formulas is on a scale of 3 which means like. The highest protein content is a formula containing 16% gude and tempeh flour, which is about 6 grams of protein/100 grams of drink. A serving of functional drink (250 g) contains about 15 g of protein. Keywords : Protein, acceptability, functional drinks, gude beans, tempeh